Heteroleptic Copper Photosensitizers: Why an Extended π‐System Does Not Automatically Lead to Enhanced Hydrogen Production. Issue 2 (1st December 2016) - Heberle, Martin; Tschierlei, Stefanie; Rockstroh, Nils; Ringenberg, Mark; Frey, Wolfgang; Junge, Henrik; Beller, Matthias; Lochbrunner, Stefan; Karnahl, Michael
Abstract: A series of heteroleptic copper(I) photosensitizers of the type [(P^P)Cu(N^N)] + with an extended π‐system in the backbone of the diimine ligand has been prepared. The structures of all complexes are completely characterized by NMR spectroscopy, mass spectrometry, and X‐ray crystallography. These novel photosensitizers were assessed with respect to the photocatalytic reduction of protons in the presence of triethylamine and [Fe3 (CO)12 ]. Although the solid‐state structures and computational results show no significant impact of the π‐extension on the structural properties, decreased activities were observed. To explain this drop, a combination of electrochemical and photophysical measurements including time‐resolved emission as well as transient absorption spectroscopy in the femto‐ to nanosecond time regime was used. Consequently, shortened excited state lifetimes caused by the rapid depopulation of the excited states located at the diimine ligand are identified as a major reason for the low photocatalytic performance. Abstract : Too much π? The extension of the π‐system at the backbone of the diimine ligand within a series of heteroleptic copper photosensitizers has a strong impact on the light‐driven reduction of protons. The origin of this behavior was studied by a combination of different photophysical and electrochemical techniques, which revealed a connection with the excited state lifetime.